Advanced Materials (Ceramics in particular) for Structural Applications - Koduru, Hari Krishna; Bartolino, Roberto; Versace, Carlo; Scaramuzza, Nicola (My University, 2015)
The study of ‘Intrinsic and Metal nano particles doped polymer thin films for soft matter applications and nanostructured Hyperbolic metamaterials’ is an challenging and dynamic field of research with significant implications in the development of novel technologies, like gas sensors, bio-medical application and engineering of spontaneous emission of florescent molecules. In the present investigation, we presented research work in two directions. We prepared Polymer thin films by homemade Cold Plasma Polymerization technique and studied their Microstructural, Optical and dielectric responses as a function of thin film growth parameters, in view of gas sensor applications. In other direction, we fabricated lamellar structured Hyperbolic Metamaterials by employing physical and chemical vapour thin film deposition techniques and employed them as effective substrates to engineer the life time of florescent dye molecules. The first part of this thesis is devoted to preparing Polypyrrole (PPy) thin films of nano sized thickness, by Cold plasma polymerization technique and analyzing the influence of Plasma power on Microstructural, Optical, wetting and dielectric properties of grown PPy films. Fabricating layered structures of “PVA/AgNPs/PVA” thin films to investigate the influence of rate of distribution of AgNPs on dielectric responses of PVA matrix to employ them as a gas sensor applications, whose study is still open and is getting substantial interest in industrial and academic environments. Enhancement of spontaneous emission is a dynamic and challenging fundamental quantum phenomenon in optics and in nutshell it opens new avenues for spectrum of futuristic applications. Metamaterials are artificially designed nanocomposite materials, in which bulk electromagnetic properties arise due to underlying structural resonances and near field coupling between the designed sub-wavelength building blocks. Metamaterials promise to alleviate the classical limitations of optics and led to exotic applications such as negative refraction, sub-wavelength resolution imaging, invisibility devices and perfect absorbers. In the second part of this thesis, we fabricated Hyperbolic metamaterials and proposed new grating coupled hyperbolic metamaterial (GCHMM) configuration for the enhancement of spontaneous emission rate of dye molecules by exploiting the unique property of a hypergrating to outcouple and extract the non-radiative plasmonic modes.
Doctorof Philosophy in Science and Technology of Mesophases and Molecular Materials, "Bernardino Telesio" Ciclo XXVIII SSD, a.a. 2015-2016
Keywords: Plasma polymerization; Plastic films; Nanotechnology